2022
DOI: 10.1111/tbed.14620
|View full text |Cite
|
Sign up to set email alerts
|

Distribution and diversity of dog parvoviruses in wild, free‐roaming and domestic canids of Newfoundland and Labrador, Canada

Abstract: Some parvoviruses of carnivorans can infect multiple host species. Since many canine parvoviruses were only discovered recently, their host-range is still unexplored. We examined the host distribution and diversity of five dog parvoviruses in four canine populations from Newfoundland and Labrador, Canada, and investigated the potential for these viruses to cross the species barriers. Canine bocavirus 2 (CBoV-2) and the minute virus of canines were detected in stool from free-roaming dogs from Labrador (5/48 [1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
20
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 64 publications
3
20
2
Order By: Relevance
“…In this study, Cachavirus has a higher prevalence and a larger geographical spread in northeastern China. The overall positive rate was 6.8%, which is higher than the previous report in China (1.55%) [16] and the two recent studies in Canada, which are 2.6% [15] and 3.3% [17], respectively. This survey included four provinces in the whole northeastern China, where Cachavirus spread over a larger geographical area and demonstrated a higher prevalence than in previous studies.…”
Section: Discussioncontrasting
confidence: 70%
See 1 more Smart Citation
“…In this study, Cachavirus has a higher prevalence and a larger geographical spread in northeastern China. The overall positive rate was 6.8%, which is higher than the previous report in China (1.55%) [16] and the two recent studies in Canada, which are 2.6% [15] and 3.3% [17], respectively. This survey included four provinces in the whole northeastern China, where Cachavirus spread over a larger geographical area and demonstrated a higher prevalence than in previous studies.…”
Section: Discussioncontrasting
confidence: 70%
“…Cachavirus was rst detected in dogs, but it was also detected in cats in 2018-2019 [16]. In the latest study, Cachavirus was also found in wild animals such as coyotes [15,17]. And they indicated that Cachavirus has been circulating at least 10 years among wild animals.…”
Section: Discussionmentioning
confidence: 99%
“…The introduction of an Asian CPV-2c strain in Europe through dog importation in 2017, and its rapid spread in the following years, both in domestic dogs and wild carnivorans, has been documented in Italy [ 12 , 13 , 14 ]. In recent years, the Asian CPV-2c variant was reported in another European country [ 15 ], as well as in Africa [ 16 ] and North America [ 17 ], supporting its progressive worldwide spread in the canine population. Nonetheless, the CPV-2a/2b strains that have been prevalent for many years in Asia have not been reported in Europe as of yet.…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade, several studies have analyzed the spread of CPV-2 in domestic and wild carnivorans in Italy [ 11 , 12 ] and documented the introduction and rapid diffusion of CPV-2c strains of Asian origin (Asian CPV-2c-like strains) in the Italian canine population [ 13 , 14 ]. These strains, which have now been detected worldwide [ 15 , 16 , 17 ], are characterized by a specific set of mutations in both structural and non-structural proteins and are phylogenetically related to each other.…”
Section: Introductionmentioning
confidence: 99%
“…Over the recent years, five different antigen variants of parvovirus have emerged around the globe, which is dangerous for many animals, and new variants express pathogenity also toward felines. Despite presence of highly specific diagnostics and effective vaccines, outbreaks of parvovirus have been recorded all around the world, characterized by novel antigen variants and broadening of the range of susceptible animals and low efficacy of vaccination (Canuti et al, 2022;Singh et al, 2022). Parvoviruses (from Latin parvus -small) comprise a group of pathogenic viruses which poses a threat to both vertebrates and insects.…”
Section: Introductionmentioning
confidence: 99%